Long-standing inhaled foreign bodies in children: Characteristics and outcome. (November 2016) - Martin, Andrew; van der Meer, Graeme; Blair, Dora; Mahadevan, Murali; Neeff, Michel; Barber, Colin; Mills, Nicola; Salkeld, Lesley; Gruber, Maayan
Abstract: Objective: Aspirated foreign bodies in children present a potentially life-threatening condition and can be challenging to diagnose. This study aims to elucidate the characteristics and outcome of children with long-standing aspirated foreign bodies. Methods: Retrospective case series of all cases of confirmed long-standing aspirated foreign bodies (LSAFB) between January 2003 to December 2015 in a single paediatric tertiary-level institution, defined as more than two weeks from choking episode or beginning of symptoms. Results: Clinical files and operative records on 227 patients were screened and 35 children were confirmed to have been treated for LSAFB as per definition above. Median time to presentation was 4 weeks (mean 8.8 weeks). Eighty-six percent presented with cough and 51% with dyspnoea. Abnormal chest X-ray findings were found in 28 out 31 patients (90%). Organic foreign bodies (22) were more common than inorganic (14). Intraoperative granulation tissue was demonstrated in 89% of patients and in 46% of patients this was regarded as significant (defined as obstructing more than 50% of the involved airway lumen). Mean length of stay was 2.5 days. Nine patients (26%) had 11 respiratory complications; there were no mortalities. Conclusions: Paediatric LSAFB poses an uncommon diagnostic dilemma as there is often no witnessed history of aspiration event; and signs, symptoms and chest X-Ray findings are often non-specific. Laryngobronchoscopy is made more difficult by the presence of granulation tissue and the sequelae of prolonged non-treatment is a higher rate of chronic respiratory disease.